Factors Influencing Customer Trust in Financial Institutions: A Systematic Literature Review - Sumariani, Ni Putu Ayu (Global Researcher Network, 2025)
This study aims to systematically examine the key factors that influence customer trust in financial institutions through a comprehensive review of relevant literature published between 2019 and 2024. Using the Systematic Literature Review (SLR) method, this research identifies and analyzes the influence of service quality, communication, and institutional reputation on customer trust, as well as the mediating role of customer satisfaction. The findings indicate that consistent service delivery, clear and transparent communication, and a strong organizational reputation significantly enhance customer satisfaction, which in turn strengthens trust in financial institutions. Furthermore, the study adopts the Theory of Planned Behavior (TPB), Trust Theory, and Customer Satisfaction Theory to develop a conceptual framework that explains the interrelationships between these variables. This research provides strategic insights for financial service providers and policymakers to enhance customer trust by focusing on service excellence, responsive communication, and reputation management. It also offers an agenda for future research, particularly on integrating cultural and demographic variables that may moderate customer trust in different financial contexts.